2022
DOI: 10.1097/qad.0000000000003261
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lymph node fine needle aspiration for the diagnosis of HIV-associated lymphoma in a low-resource setting

Abstract: Objective:Fine needle aspiration (FNA) is an early step in the work-up of lymphadenopathy in people with HIV (PWH). We set out to characterize the FNA cytology in PWH and report on the time to lymphoma diagnosis through the FNA clinics in the public healthcare system in Johannesburg, South Africa.Design:Retrospective review of laboratory database.Methods:A retrospective chart review of patients undergoing FNA through the department of cytopathology at the National Health Laboratory Service (NHLS) was undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…In a recent South-African publication, the linkage to care following an FNAC suspicious for lymphoma was abysmal: of 45 PWH with cytology suggestive of lymphoma, only 24 (53%) returned for a biopsy confirming the diagnosis. Among the patients lost to follow-up at the one-year timepoint, 57% had died, 29% were untraceable, and only 14% were confirmed alive [21]. We stopped performing cytology early in our 592 AIDS 2023, Vol 37 No 4 study due to poor diagnostic yield for lymphoma, even though the aspirate came from the same site as a biopsy (i. e., confirming representative tissue), and best-practice guidelines were followed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent South-African publication, the linkage to care following an FNAC suspicious for lymphoma was abysmal: of 45 PWH with cytology suggestive of lymphoma, only 24 (53%) returned for a biopsy confirming the diagnosis. Among the patients lost to follow-up at the one-year timepoint, 57% had died, 29% were untraceable, and only 14% were confirmed alive [21]. We stopped performing cytology early in our 592 AIDS 2023, Vol 37 No 4 study due to poor diagnostic yield for lymphoma, even though the aspirate came from the same site as a biopsy (i. e., confirming representative tissue), and best-practice guidelines were followed.…”
Section: Discussionmentioning
confidence: 99%
“…The study highlights the need to improve the diagnostic pathway for lymphoma in low-resource settings and discusses potential interventions, such as upfront lymph node resection or upfront core-needle biopsy and the incorporation of molecular studies to expedite diagnosis and treatment decisions. 27…”
Section: Fnab Of Lymph Nodesmentioning
confidence: 99%
“…Within a low-resource environment with high TB prevalence, Vogt et al [13] report their results of a retrospective study of FNAs performed in PWH in this issue of AIDS. Vogt et al [13] identified 539 lymph node a FNAs performed in PWH presenting to an FNA clinic that were reviewed by the National Health Laboratory Service (NHLS) in Johannesburg, South Africa over a 3-month period in 2018. As standard practice in NHLS, all lymph nodes underwent additional testing for drug-susceptible and multidrug-resistant TB with a PCR platform.…”
mentioning
confidence: 99%
“…This study by Vogt et al [13] highlights the need for scaleup of pathology services for the diagnosis of HIVassociated cancers in low-income and middle-income countries (LMICs) and the linkage of diagnosis to cancer care. The number and specialty training of pathologists as well as adequate laboratory support for sample processing are lacking in many LMICs, leading to likely underdiagnosis or misdiagnosis of lymphomas [15,16].…”
mentioning
confidence: 99%
See 1 more Smart Citation